Perencanaan Strategis Sistem Informasi Pada Madrasah Aliyah Nurussa’adah Sarolangun - Putri Sabila , Wilda; Assegaff , Setiawan (LPPM Universitas Dinamika Bangsa, 2023)
Madrasah Aliyah Nurussa'adah Sarolangun has a need for IS/IT to be able to adapt to the existing environment. There is no integrated information system development plan so information system development is only based on current needs without considering further development. Based on the existing problems, the author proposes strategic planning of information systems with the Ward and Peppard method where this method emphasizes the analysis on increasing competitiveness and threats. The analysis is carried out using various tools critical success factor, value chain, SWOT, McFarlan Strategic Grid, and five forces. The results of this study are a strategic planning of information systems in the form of a portfolio of future applications that can support business processes, IS/IT management strategies which can help Madrasah Aliyah Nurussa'adah Sarolangun to increase competitiveness, optimize human resources, and utilize information systems and technology. future information for Madrasah Aliyah Nurussa'adah Sarolangun.